Hubungan Tingkat Pengetahuan Pasien Diabetes Mellitus dengan Perawatan Luka Menggunakan Tekhik Modern Dressing (Studi RLS Sidoarjo) - Sukmawati, Ermalynda; Sari, Nia Novita; Chriswinda B.M, Agustina (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2019)
Diabetes Mellitus is a progressive chronic metabolic disease, with clinical manifestations of glucose and disorders of lipid metabolism, accompanied by chronic complications of narrowing of arteries, due to decreased function of organ damage (Black, 2014). The design in this study was pre-experimental with a one shot case study design. Samples are patients who come for wound care with modern dressing techniques and routine blood sugar checks. The sample was chosen by purposive sampling, the sample size was 25. The results of the product moment correlation test were used not to analyze the data significantly (p <0.312). The majority of respondents in this study were women (60%), 45-59 years (60%), senior high school (32%), private employment (52%), duration of suffering from diabetes mellitus 1-3 years (80%), and wounded diabetes mellitus (96%). Knowledge and treatment of wounds with modern dressing techniques significantly (p <0.129). Increased knowledge of respondents regarding wound care by using modern dressing techniques affect respondents to increase knowledge about diabetes mellitus with wound care using modern dressing techniques, conclusions in sufficient knowledge about diabetes mellitus and wound care using modern dressing techniques.Â Keywords: Diabetes Mellitus, Knowledge, Wound Care, Modern Dressing Techniques.